The use of multivariate analysis to characterize carcass and meat quality of goat kids protected by the PGI "Cabrito de Barroso" - Santos, Virgínia (2012)
Fifty five suckling kids from three genotypes and two sexes protected by the PGI "Cabrito de Barroso" European quality label were used in this experiment. Carcass quality was assessed using indices from carcass measurements, dressing percentages, refrigerated losses, higher priced joints proportion and tissue composition of the carcass. Meat pH, colour, total pigment, fat, dry matter, collagen determinations (total and soluble), cooking losses and shear force estimated in longissimus thoracis et lumborum (LTL) and gluteobiceps (GB) muscles were used to characterize meat quality. Principal component (PC) analysis was performed in order to examine carcass quality traits (n = 16) and meat quality (n = 16) traits. The five first principal components (PCs) explained about 86% of the total variability for carcass quality and 75% of the total variability for meat quality. Compactness indices of carcass and leg, carcass weight and subcutaneous fat were the most effective variables for the PC 1, whereas the higher priced joints proportion, muscle proportions of the higher priced joints and of the carcass and the muscle and bone ratio were useful to define the PC2. The first PC of the meat quality parameters was characterized by colour traits (L*, b*, a*, C*, H* and total pigment) whereas collagen determinations (total collagen and collagen solubility) defined the second PC. When the carcass quality data were projected on the plane defined by the first two PCs, two separate groups of points appeared, corresponding to the animals with slaughter live weight higher or lower than 10 kg. The distribution of the meat quality data on the plane defined by the first two PCs allowed the identification of two separate groups, corresponding to the muscles GB and LTL. The differences between genotypes tend to be small and related to slaughter live weight, which implies certain constancy in carcass and meat quality of the PGI "Cabrito de Barroso".